The RANCANG BANGUN MODUL ALAT PELATIHAN KESELAMATAN LISTRIK AC/DC DALAM PENCEGAHAN BAHAYA KELISTRIKAN DAN LEDAKAN - Novita Lizza Anggraini; Naufal Nibraas N.H; Andhika Giyantara; Himawan Wicaksono; Mayati Isabella; Lusia Salmawati; Maulana Ibrahim; Tama Riska Br Sembiring (SPECTA Journal of Technology, 2026)
Based on Law Number 1 of 1970 concerning Occupational Safety is not only applied in industry, but in all workplaces, it is mandatory to apply Safety and Security (K3), one of which is in education both at school and college levels which have a high risk of danger. The cause of work accidents occurs due to Unsafe Action factors reaching 88% and 10% Unsafe Conditions. Health and Safety Executive data states that 90% of accidents are caused by human error. The purpose of the research is to design AC and DC electrical safety training modules that can be used as practicum media for students in understanding the basic principles of electrical risk control and prevention of explosion hazards due to errors in electrical systems. The engineering and development method is the design and fabrication of training modules, which consist of AC and DC electrical devices, equipped with risk control systems such as automatic circuit breakers, grounding systems, and short circuit protection. The results show that the circuit design consists of 2 circuits, namely AC and DC circuits. The circuits can be separated and can be combined by considering making it easier to carry out practicum and maintenance processes to prevent failures in the system that can cause accidents.